Antibacterial and Antibiofilm Effects of Ziziphus mauritiana Leaf Extract Against Staphylococcus aureus - Poedjiastoeti, Wiwiek; Rasad, Irvan Septrian Syah Putra; Tanzil, Felicia Klarissa; Gunardi, Indrayadi; Widyarman, Armelia Sari (UI Scholars Hub, 2026)
Background: Tooth extraction is a common dental procedure often complicated by postoperative infections, with Staphylococcus aureus as a key opportunistic pathogen. Rising antibiotic resistance and side effects of conventional antiseptics like chlorhexidine highlight the need for natural alternatives. This study evaluated the antibacterial and antibiofilm potential of 96% ethanol extract from Ziziphus mauritiana leaves against S. aureus. Methods: The extract was prepared by maceration and tested in vitro using microdilution for minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) against S. aureus ATCC 25923. Antibiofilm activity was assessed via crystal violet staining on mature biofilms, with confirmation by qPCR-based absolute quantification of bacterial load using S. aureus-specific 16S rRNA primers. Statistical analysis included Shapiro–Wilk, ANOVA, and Tukey HSD tests. Results: The extract showed MIC between 125–250 mg/mL and MBC at 250 mg/mL. Concentrations of 1000, 500, and 250 mg/mL inhibited >80% biofilm biomass, comparable to 0.2% chlorhexidine. qPCR confirmed significant bacterial load reduction at 1000 and 500 mg/mL. Conclusions: Z. mauritiana leaf extract demonstrates promising antibacterial and antibiofilm activity against S. aureus, supporting its potential as a natural agent for managing post-extraction infections, though further studies on clinical isolates, cytotoxicity, and formulations are warranted.